Growth rate of diamond-like coatings synthesized in RF discharge at various ratios of the concentrations of Ar and C₆H₆ - Kalinichenko, A.I.; Omarov, A.О.; Strel’nitskij, V.E. (Вопросы атомной науки и техники, 2021)
Diamond-like coatings (DLC) synthesized by plasma-chemical deposition from a vapor mixture of C₆H₆ and Ar have been investigated. The growth rate of the coating was measured, which showed a nonlinear dependence on the partial pressure of Ar. The mathematical model of the deposition has been developed, which qualitatively and quantitatively describes the dependence of the ion flux density and deposition rate on the partial pressure of argon. Досліджено алмазоподібні покриття, які отримані плазмохімічним осадженням з парової суміші C₆H₆ і Ar. Виміряна швидкість росту покриття, яка показала нелінійну залежність від парціального тиску Ar. Розроблено математичну модель осадження, що якісно і кількісно описує залежність густини потоку iонiв та швидкості осадження від парціального тиску аргону. Исследованы алмазоподобные покрытия, полученные плазмохимическим осаждением из паровой смеси C₆H₆ и Ar. Измерена скорость роста покрытия, которая показала нелинейную зависимость от парциального давления Ar. Разработана математическая модель осаждения, качественно и количественно описывающая зависимость плотности потока ионов и скорости осаждения от парциального давления аргона.